2022
DOI: 10.3390/nano12142349
|View full text |Cite
|
Sign up to set email alerts
|

Tomato Fruit Nutritional Quality Is Altered by the Foliar Application of Various Metal Oxide Nanomaterials

Abstract: Carbohydrates and phytonutrients play important roles in tomato fruit’s nutritional quality. In the current study, Fe3O4, MnFe2O4, ZnFe2O4, Zn0.5Mn0.5Fe2O4, Mn3O4, and ZnO nanomaterials (NMs) were synthesized, characterized, and applied at 250 mg/L to tomato plants via foliar application to investigate their effects on the nutritional quality of tomato fruits. The plant growth cycle was conducted for a total of 135 days in a greenhouse and the tomato fruits were harvested as they ripened. The lycopene content … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 57 publications
1
2
0
Order By: Relevance
“…The root length of tomato plants increased by 53% when treated with 10 mg L −1 MnFe 2 O 4 NP [41], which is lower than the increase observed in this study in the MnFe 2 O 4 NP-treated 12BS5076-8 maize inbred line (Table 2). On the contrary, Cantu et al [59] concluded that there was no statistical difference in root and shoot length between 250 mg/L MnFe 2 O 4 NP-treated tomato plants and control plants, which also matches a few of the results of the current study (Table 2). The results from the previous studies mentioned above show a trend that is nearly identical to that observed in the current study, although the extent of increases or decreases compared with the control differ, which may be because of differences in growth conditions, genetic variations among crop varieties, nanoparticle concentrations, and application methods.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The root length of tomato plants increased by 53% when treated with 10 mg L −1 MnFe 2 O 4 NP [41], which is lower than the increase observed in this study in the MnFe 2 O 4 NP-treated 12BS5076-8 maize inbred line (Table 2). On the contrary, Cantu et al [59] concluded that there was no statistical difference in root and shoot length between 250 mg/L MnFe 2 O 4 NP-treated tomato plants and control plants, which also matches a few of the results of the current study (Table 2). The results from the previous studies mentioned above show a trend that is nearly identical to that observed in the current study, although the extent of increases or decreases compared with the control differ, which may be because of differences in growth conditions, genetic variations among crop varieties, nanoparticle concentrations, and application methods.…”
Section: Discussionsupporting
confidence: 91%
“…It has also been reported that the chlorophyll content of mung beans increased by 14.8% after CND treatment. On the other hand, Cantu et al [ 59 ] found no significant differences in chlorophyll content between tomato plants treated with 250 mg L −1 MnFe 2 O 4 NP and their control plants. Furthermore, when MnFe 2 O 4 NP were applied to barley plants at concentrations ranging from 62.5 to 500 mg L −1 , the results showed no significant differences in chlorophyll content [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…The second paper on tomatoes, by Jason White, Jorge Gardea-Torresday and coworkers [ 6 ], studies Fe 3 O 4 , Fe 3 O 4 , MnFe 2 O 4 , ZnFe 2 O 4 , Zn 0.5 Mn 0.5 Fe 2 O 4 , Mn 3 O 4 , and ZnO nanomaterials (NMs), which were administered to tomato plants via foliar application to investigate their effects on the nutritional quality of the fruits. The plants grew for 135 days in a greenhouse, and the tomato fruits were harvested as they ripened.…”
Section: Physiological and Molecular Responses Of Plants To Engineere...mentioning
confidence: 99%